Waste Management-Based Islamic Social Entrepreneurship Model for Community Empowerment: A Bibliometric Perspective - Ansori; Abu Yasid; Siti Musfiqoh; Iskandar Ritonga; Nurhayati; Ilham (Cita konsultindo, 2026)
Waste management has emerged as a critical global issue, especially in developing countries such as Indonesia. The community-based waste processing program (TPS-3R) represents one of the government's efforts to reduce environmental burdens through community participation. However, the sustainability of this program depends on economic incentives and social acceptance. Islamic Social Entrepreneurship (ISE) offers a promising framework that integrates entrepreneurship with Islamic values such as maslahah , adl , and khalifah fil ardh , emphasizing justice, collective benefit, and stewardship of the environment. This study employs bibliometric analysis of 185 articles indexed in Scopus and Google Scholar between 2010–2024 to explore the intersection between waste management, social entrepreneurship, and community empowerment. The results show four dominant clusters: (1) community participation, (2) social entrepreneurship and innovation, (3) waste management and circular economy, and (4) Islamic values and sustainability. Research on waste management and empowerment is well established, yet studies explicitly integrating Islamic perspectives remain limited. This paper proposes a conceptual model of waste management-based Islamic social entrepreneurship for community empowerment, offering implications for scholars, policymakers, and practitioners